The Influence of Entrepreneurial Intention, Entrepreneurial Commitment, Family Support, on Entrepreneurial Behavior to Students in Bandung - Zoel Hutabarat; Evelyn Angelita (Universitas Pelita Harapan, 2025)
Students with high entrepreneurial intention but who have not yet transformed it into entrepreneurial behavior represent a contradictory issue that requires in-depth research. This study explores the influence of entrepreneurial intention, entrepreneurial commitment, and family support on the entrepreneurial behavior of students in Bandung. The study involved 193 students from three universities in Bandung using a non-probability sampling method, specifically judgmental sampling. The results of the study indicate that entrepreneurial intention has a positive influence on entrepreneurial behavior, both directly and indirectly through entrepreneurial commitment. However, entrepreneurial commitment does not have a direct influence on entrepreneurial behavior. Furthermore, family support does not provide a positive moderating effect on the relationship between entrepreneurial intention and entrepreneurial commitment. This study provides insights into the importance of entrepreneurial intention in shaping entrepreneurial behavior, despite the absence of a role for entrepreneurial commitment and family support.